Risk of dementia or Parkinson’s disease in the presence of Sjögren’s syndrome: A systematic review and meta-analysis - Wang, Zhen-Zhi; Liu, Meng-Si; Sun, Zhen; Zhang, Xu-Long; Zhang, Mei-Ling; Xiong, Kang; Zhou, Feng (Frontiers in Integrative Neuroscience, 2022)
Objective Evidence from observational studies suggests that Sjögren’s syndrome (SS) may contribute to an elevated risk of Parkinson’s disease (PD) and dementia. However, few studies have been undertaken to summarize and assess the consistency of the data quantitatively. Therefore, we evaluated the risk of dementia and PD in SS patients through a systematic review and meta-analysis approach. Methods Two reviewers independently conducted a systematic search of PubMed, Embase, and Web of Science databases (updated to February 14, 2022) to identify published literature on the association between SS and dementia or PD. The risk estimates of dementia or PD in patients with SS were pooled using fixed or random-effects models. Results Of the 631 studies initially searched, 10 were eventually included. Pooled results suggested that the risk of developing dementia significantly increased in patients with SS (HR = 1.24, 95% CI: 1.15–1.33, P < 0.001), and such risk in females with SS was similar to that in males. The risk of PD was 1.36 times higher in SS (HR = 1.36, 95% CI: 1.23–1.50, P < 0.001). The association between SS and PD risk appeared to occur primarily in female patients (female: HR = 1.28, 95% CI: 1.21–1.35; P < 0.001 vs. male: HR = 1.00, 95% CI: 0.87–1.16, P = 0.962, respectively). No significant effect of age was observed on the risk of developing PD and dementia in SS patients. Conclusion Our study supports that people with SS are at higher risk of PD and dementia than the general population. Further studies are needed to elucidate the underlying mechanisms and to assess whether interventions for SS have the potential to affect dementia and PD development.